5 Perancangan Ulang Konstruksi Girder Overhead Crane Kapasitas 10 ton Bentangan 14 meter - LUKLU'UL FITRIYAH SUSANTI; I Putu Sindhu Asmara; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Abstract - PT.BOSO makes overhead crane for vacant land that will be used as workshops. Themanufacturing of new cranes uses the size of existing crane data with a capacity of 5 tons. Size ofplate that will be uses is same and length of the span that was originally 16 m will be made into 14 m.Construction of the girder has been made, but the construction has not been realized into a crane thatcan operate because there is no calculation to analyze the strenght of the structure. This researchshows that the load that can be applied to the cnstruction of the girder is 20 tons and 18 tons for theend carriage. Due to this finding, the researcher gave 10 tons of SWL on the overhead craneconstruction. Exiting data of girder made a SS400 for material and the allowable stress is 117,5N/mm2 and the value of the stress is 59,50 N/mm2in FEM calculation with the value of the deflection10,69 mm. The result of redesign uses ST52-3 material with the administration of SWL 10 ton and theallowable stress is 177,5 N/mm2 as well as FEM calculation result with the value of the stress is 78,30N/mm2and the deflection is 13,42 mm. For the result of the girder optimazion uses SS400 materialwith the administration of SWL 10 ton and the allowable stress is 117,5 N/mm2 as well as FEMcalculation result with the value of the stress is 76,55 N/mm2and the deflection is 16.22 mm.